Further delineation of the clinical spectrum in RNU4ATAC related microcephalic osteodysplastic primordial dwarfism type I. Issue 8 (21st June 2013) - Abdel‐Salam, Ghada M.H.; Abdel‐Hamid, Mohamed S.; Hassan, Nihal A.; Issa, Mahmoud Y.; Effat, Laila; Ismail, Samira; Aglan, Mona S.; Zaki, Maha S.
Abstract We describe five patients from three different families with microcephalic osteodysplastic primordial dwarfism type I (MOPD I), which was molecularly confirmed by homozygosity for the g.51G >A and g.55G >A mutations in RNU4ATAC, respectively. The patients showed the classical phenotype and demonstrated in addition variable degrees of gyration abnormalities and malformations of the callosal body with an interhemispheric cyst. One patient also showed underdevelopment of the cerebellar vermis. This confirms that cortical malformations should be considered cardinal manifestations of MOPD I. Oculocutaneous albinism, brain hemorrhage and chilblains have been found to be associated with MOPD I. The present study showed lack of retinal pigmentation in three patients of whom two had an unusually fair complexion of hair and skin. One patient was found to have a hematoma in the left thalamus. This may indicate that both pigmentary abnormalities and vascular anomalies may be part of the phenotype of MOPD I as well. © 2013 Wiley Periodicals, Inc.